REFORMS FOR THE LAND REASSURANCE IN BENIN MASSIVE DELIVERY OF LAND TITLES - DEGBEGNON, LÉOPOLD; HOUINOU, GOSSOU (My University, 2018)
The reorganization of the sector of the land management in general and the urban land tax in particular, stays nowadays, one of the necessities that must drive to the sustainable development. To reach there, every plot of land has to have Land Title (LT). That’s why, the Government of the Republic of Benin has introduced the massive creation of Land Titles in certain urban areas of the country. During the management of this project, several difficulties have been resolved while others continue. Most of these difficulties find their foundation in the essence and the tenures characterizing the beninese land system. That’s why it will be necessary to regulate them by reforms as legislative as institutional and structural.
Keywords: Title land tax; transfer; rightful claimant; land security; land registry